“Person” in CIC and CCEO Matrimonial Law. On the Idea of Vetera et Nova Harmonization in the Church Doctrine and Jurisprudence - Pastwa, Andrzej (Philosophy and Canon Law, 2021)
serious confrontation with the subject: “Person” in the Code of Matrimonial Law (CIC and CCEO), is an—invariably relevant—challenge that the study of canon law and jurisprudence have to face. The argument for the validity of this conclusion is provided by the famous John Paul II’s thesis, proclaimed in the Familiaris Consortio exhortation (1981) and the famous 1997 Address to the Roman Rota, which can be summarized in the following words: the foundation and structural principle of interpersonal (ethical and legal!) relationships in marriage is matrimonial love. This axiom—still insufficiently present in the thoughts of canonists and church judges—reflects the deepest truth, of which “prophetically” the author of the monumental works Love and Responsibility and The Acting Person gave testimony; the truth that not elsewhere, but in the conciliar spiritually person-centric vision of matrimonial community (communio/consortium), a hermeneutic key should be sought for an adequate and complete understanding of the structure of marriage, harmoniously integrating its two personal and institutional dimensions. Karol Wojtyła’s/John Paul II’s brilliant thought deserved to be confronted with the premises that prove the hypothesis that the mere declarative identification in the expressed judgments/concepts with the idea of a personalistic aggiornamento (“programmed” especially in numbers 47–52 of the Council’s Constitution Gaudium et Spes) does not yet guarantee the adequacy and completeness of the canonistic approaches to the “truth of matrimony.” This is both in the sphere of theological exposure in accordance with the Magisterium (in the light of the “Image of God”) and at the praxis level: the interpretation and application of the normative records in the nodal canons of CIC and CCEO. The first part of the study is dedicated to illustrating such a state of affairs – in various proposals of doctrine and jurisprudence: from a concept that is completely misguided and destined to fail in advance; through a concept that, because of its extremely conservative approach to the need for vetera et nova harmonisation, has not stood the test of time, to concepts, indeed, universally acknowledged in the study of canon law, whose authors (or their adherents), after all, should be suggested to implement certain necessary corrections: bigger or smaller. In the second part, the research contemplation focuses on the conclusions of the realization of the conciliar postulate of “harmonization” in presenting a person-centric vision of matrimony. These synthetic remarks constitute an attempt to show the basis for an adequate interpretation of the formula adopted by the two codes announced in the title: “a partnership of the whole of life”.